Effects of blood flow restriction training on cardiopulmonary function and body composition: a systematic review with meta-analysis - Yang, Kun; Chee, Chen Soon; Abdul Kahar, Johan; Tengku Kamalden, Tengku Fadilah; Li, Rui; Qian, Shaowen (Termedia Publishing House Ltd., 2026)
The aim of this meta-analysis was to investigate the effects of blood flow restriction training (BFRT) on cardiopulmonary function and body composition of athletes and active participants. Based on the PRISMA guidelines, we searched four international databases for literature up to November 2024, assessed methodological quality using the PEDro scale, and used RevMan 5.4 software for data analysis, publication bias evaluation as well as subgroup analysis. A meta-analysis of forty well-assessed quality studies involving a total of 839 athletes and active participants aged 14– 33 years was conducted. The results revealed that BFRT moderately improved both pulmonary function (ES = 0.81–0.88; p < 0.01) and muscle hypertrophy (ES = 0.73–0.74; p < 0.01), while no significant improvement was found for cardiac function (ES = −0.30–0.35; p > 0.05) and anthropometric measures (ES = 0.02–0.04; p > 0.05). Subgroup analyses showed that the moderator variables (training status, age, duration, frequency, training type, and cuff pressure) also had small to large significant effects on pulmonary function and muscle hypertrophy (ES = 0.55–1.74; p < 0.05). In conclusion, BFRT positively affected cardiopulmonary function and body composition in athletes and active participants with significant improvements in pulmonary function and muscle hypertrophy, but not in cardiac function and anthropometric measures. BFRT was more beneficial for improving these physiological metrics when applied to young trained participants with intervention duration of less than six weeks and frequency of fewer than three sessions per week..